Determination of Trace Mercury in Chinese Herbal Medicine by Cold Vapour Generation - Atomic Fluorescence Spectrometry - Chen, Yijian; Dong, Xuechang; Dai, Yun; Hu, Qiufen; Yu, Hong (Asian Journal of Chemistry, 2010)
A highly sensitive and simple method was developed for the simultaneous determination of trace mercury in Chinese Herbal Medicine by cold vapour generation-atomic fluorescence spectrometry. The herbal medicine samples were digested by closed microwave digestion with HNO3 + H2O2 (1:1). The digested samples were determined by cold vapour generation-atomic fluorescence spectrometry equipped with an atomizer which effectively improved the stability of the signals. The conditions for the generation of volatile mercury species were investigated in detail. The tolerance to the interference of coexisting ions was carefully examined. Under optimal conditions, the detection limits (3s) were evaluated to be 4.2 ng L-1 for mercury. This method was successfully applied to the determination of mercury in Chinese Herbal medicine samples (Hg in the range of 24 to 83 μg kg-1). The relative standard deviations are 2.5-2.8 %. The recoveries are 94-104 %.